Synergistically acting agonists and antagonists of G protein-coupled receptors prevent photoreceptor cell degeneration - Chen, Yu; Palczewska, Grazyna; Masuho, Ikuo; Gao, Songqi; Jin, Hui; Dong, Zhiqian; Gieser, Linn; Brooks, Matthew J; Kiser, Philip D; Kern, Timothy S; Martemyanov, Kirill A; Swaroop, Anand; et al. (Science signaling, 2016)
Photoreceptor cell degeneration leads to visual impairment and blindness in several types of retinal disease. However, the discovery of safe and effective therapeutic strategies conferring photoreceptor cell protection remains challenging. Targeting distinct cellular pathways with low doses of different drugs that produce a functionally synergistic effect could provide a strategy for preventing or treating retinal dystrophies. We took a systems pharmacology approach to identify potential combination therapies using a mouse model of light-induced retinal degeneration. We showed that a combination of U.S. Food and Drug Administration-approved drugs that act on different G protein (heterotrimeric guanine nucleotide-binding protein)-coupled receptors (GPCRs) exhibited synergistic activity that protected retinas from light-induced degeneration even when each drug was administered at a low dose. In functional assays, the combined effects of these drugs were stimulation of Gi/o signaling by activating the dopamine receptors D2R and D4R, as well as inhibition of Gs and Gq signaling by antagonizing D1R and the α1A-adrenergic receptor ADRA1A, respectively. Moreover, transcriptome analyses demonstrated that such combined GPCR-targeted treatments preserved patterns of retinal gene expression that were more similar to those of the normal retina than did higher-dose monotherapy. Our study thus supports a systems pharmacology approach to identify treatments for retinopathies, an approach that could extend to other complex disorders.